THE DIFFERENCE OF MORAL MATURITY TOWARD TO STUDENT OF ISLAMIC SENIOR HIGH SCHOOL AND STUDENT OF SENIOR HIGH SCHOOL: Comparative Studies between school based on religion and school based on public (PERBEDAAN KEMATANGAN MORAL PADA SISWA MA DAN SMA: Studi Ko - Latifatul Masruroh (Fakultas Agama Islam Universitas Wiralodra Indramayu, 2019)
The article aims to describe the moral maturity to student of MA and student of SMA. Religion moral is one of ht moral must be actualized to teenager since childhood The guidance processes of teenagers have an effective effect to the moral maturity. In this case, the parent, school, and environment, influence the moral formation process. In the school, the teenagers spend their time about 8 hours, they interact with the other teenagers and their teachers and the staff of the school. The basic, school policy and moral values give more significance influence toward moral maturity of teenagers or students. Artikel ini bertujuan untuk mendeskripsikan kematangan moral pada siswa MA dan siswa SMA. Moral agama merupakan salah satu moral yang harus diaktualisasikan kepada remaja sejak usia dini. Pada faktanya menunjukan bahwa Proses bimbingan remaja memiliki efek yang efektif terhadap kematangan moral. Dalam hal ini, orang tua, sekolah, dan lingkungan, memengaruhi proses pembentukan moral. Di sekolah, para remaja menghabiskan waktu mereka sekitar 8 jam, mereka berinteraksi dengan remaja lain dan guru-guru mereka dan staf sekolah. Dasar, kebijakan sekolah dan nilai-nilai moral memberikan pengaruh yang lebih signifikan terhadap kematangan moral remaja atau siswa.